The Logical Problem and the Theoretician's Dilemma. (7th September 2016) - Clatterbuck, Hayley
Abstract : The theory‐theory of human uniqueness posits that the capacity to theorize, in a way strongly analogous to theorizing in scientific practice, was a key innovation in the hominid lineage and was responsible for many of our unique cognitive traits. One of the central arguments that its proponents have used to support the claim that animals are not theorists, the logical problem, bears strong similarities to Hempel's theoretician's dilemma, which purports to show that theories are unnecessary. This similarity threatens to undermine both the claim that theorizing serves a unique, adaptive role in human cognition and our ability to test for the presence of theories. I examine two historical responses to the theoretician's dilemma and argue that they open up strategies for experimentally testing for theoretical ability in other animals.